Deep Convection as Inferred From the C2OMODO Concept of a Tandem of Microwave Radiometers - Auguste, Franck; Chaboureau, Jean-Pierre (Frontiers in Remote Sensing, 2022)
Probing the atmosphere from space using radiometers is a challenging way to improve our knowledge of deep convection. Exploration of the water absorption bands in the 183, 325 and 448~GHz range is promising because of the radiation scattered by icy hydrometeors produced by deep convection. We investigate what properties of deep convection could be inferred from the Convective Core Observations through MicrOwave Derivatives in the trOpics (C2OMODO) concept of a tandem of microwave radiometers separated by several tens of seconds. Two tropical deep convective events (Hector the Convector and a radiative-convective equilibrium case) are simulated with the Meso-NH non-hydrostatic numerical model, the outputs of which are used to compute brightness temperatures (Tbs) using the Radiative Transfer for the Television and Infrared Observation Satellite (TIROS) Operational Vertical Sounder (RTTOV) code. We find different relationships between ice water path, vertical ice momentum and vertical ice velocity and the time derivative dTb/dt. They depend on where they probe after separating the growing convective cores from their surrounding environment with a radiometric point of view. Tb and dTb/dt are highly dependent on the ice water path that depends on horizontal and vertical ice advection and microphysical processes. Looking at deep convection in general, we find that the ice water path increases linearly with decreasing dTb/dt. In the specific case of the core of growing convective cells, the vertical ice momentum and the vertical ice velocity are related to dTb/dt. However, such a relationship breaks down in the anvil because horizontal ice advection can dominate microphysical processes. These results are robust to horizontal resolution and time delay.